Control and Synchronization of Chaotic and Hyperchaotic Lorenz Systems via Extended Backstepping Techniques. (6th May 2014) - Onma, O. S.; Olusola, O. I.; Njah, A. N.
Abstract : We propose novel controllers for stabilization and tracking of chaotic and hyperchaotic Lorenz systems using extended backstepping techniques. Based on the proposed approach, generalized weighted controllers were designed to control chaotic behaviour as well as to achieve synchronization in chaotic and hyperchaotic Lorenz systems. The effectiveness and feasibility of the proposed weighted controllers were verified numerically and showed their robustness against noise.